Emotional Intelligence as a Mediating Mechanism between Lecturer Competence and Innovation - Luluh Abdilah; Suhaily Shahimi; Yuyus Yudistria; Isni Andriana; Nova Rina (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Improving the quality of higher education requires strengthening lecturers’ competence and innovative behavior in response to digital transformation and the demands of Industry 4.0. This study examined the mediating effect of emotional intelligence in the relationship between lecturer competence and lecturer innovation at private universities under the coordination of LLDIKTI Region IV. A quantitative approach was employed using structured questionnaires distributed to lecturers in private universities across Bogor, Depok, Tangerang, and Bekasi. A total of 354 responses were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results indicate that lecturer competence has a positive and significant effect on lecturer innovation, both directly and indirectly through emotional intelligence. The mediation analysis confirms that emotional intelligence strengthens the relationship between competence and innovation, serving as a key psychological mechanism that translates professional competence into innovative behavior. These findings suggest that universities should incorporate emotional intelligence development into lecturer capacity-building programs to promote sustainable innovation and academic excellence.